Comparative Analysis of Interfacial Adaptation and Depth Penetration of Recent HiFlow versus Regular Bioceramic Sealers in Conjunction with BC Gutta-Percha Points Using Two Different Obturation Techniques—A Preliminary Report of an Ex Vivo Study - Sawsan T. Abu-Zeid; Ruaa A. Alamoudi (Journal of Functional Biomaterials, 2024)
This study aimed to assess the adaptability and penetration depth capacity of recent bioceramic systems, including regular EndoSequence (BC) versus HiFlow (BCH) sealers in the presence of BC points. A total of 54 single-rooted teeth were instrumented and obturated with either the cold or warm compaction technique (n = 9), using either BC, BCH, or AH Plus (AHP) combined with BC points. The adaptation, film thickness, and gaps/voids were evaluated by scanning electron microscopy. The sealer/dentin interface was evaluated by Raman spectroscopy, and depth penetration was evaluated by a confocal laser scanning microscope. According to the normality test, the data were statistically analyzed by ANOVA or Kruskal–Wallis and Mann–Whitney U tests at p < 0.05. BCH sealer showed the significantly thinnest film with the greatest flow (p > 0.001), with further improvement when subjected to the warm compaction technique. Moreover, it exhibited close adaptation with deep penetration into radicular dentin, forming a tag-like structure. The Raman spectra also indicated close contact with the dentin surface. The use of BC sealer with BC points exhibited homogenous, single-unit obturation, either with a cold or warm technique. Furthermore, the use of the warm compaction technique with BCH sealer achieved a gap-free interface associated with tag-like structures, which exhibit the monoblock phenomenon.